Necrotizing pancreatitis after removal of prophylactically placed pancreatic stent - Sridhar Sundaram (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Sundaram S. Necrotizing pancreatitis after removal of prophylactically placed pancreatic stent. Turk J Gastroenterol 2019; 30(11): 991-2.